Die Wahrnehmung des gesetzlichen Hautkrebsscreenings in der Allgemeinbevölkerung: aktuelle Erkenntnisse über Teilnahmequote, Kenntnisstand und Beurteilung = Perception of statutory skin cancer screening in the general population - Eissing, Leah; Enk, Alexander (Der Hautarzt, 2017)
Background: Since 2008, German statutory health insurances offer routine skin cancer screening (rSCS) as a standard benefit. Insured persons aged 35 years and older are eligible for screening every 2 years. Objectives: The aim of the study was to evaluate perception and utilization of rSCS in the general population. Materials and methods: A representative random sample of n = 1004 adult members of the German statutory health insurances were surveyed by the Forsa Institute via computer-assisted telephone interviews in a cross-sectional study in April 2015. Results: On 39% of all persons interviewed, skin cancer screening had been executed at least once; the percentage of those entitled for rSCS was 45%. Of the participants, 50% were aware of the rSCS eligibility framework, with multiple sources of information. In 82% of cases, rSCS was performed by a dermatologist. The majority (87%) of those who had already undergone rSCS stated that the advantages of the procedure outweighed inconveniences. While participation in rSCS constantly increased (2011-2013-2015), knowledge of eligibility did not. Conclusions: Seven years after implementation, rSCS has been utilized by almost half of those entitled and was rated positively by the majority. However, lack of knowledge about rSCS eligibility is also present in 50%. Further targeted informative measures are needed to increase awareness of rSCS.